2017
DOI: 10.1080/08039488.2017.1340518
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor serum and plasma levels in the treatment of acute schizophrenia with olanzapine or risperidone: 6-week prospective study

Abstract: Antipsychotics have been the mainstay of the treatment of schizophrenia, and their potential role in neuroprotection could be related to brain-derived neurotrophic factor (BDNF). So far different effects on both serum and plasma levels of BDNF were reported related to the various antipsychotic treatments. Aim of this study was to investigate the influence of olanzapine or risperidone on both plasma and serum levels of BDNF in patients with acute schizophrenia. For 50 participants with acute episode of schizoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Remarkably, drug treatment that is effective in controlling disease progression in schizophrenic patients can have diverse effects on peripheral BDNF protein levels [ 126 128 ]. In addition, some studies suggest that baseline BDNF levels in schizophrenia patients might reflect the susceptibility towards available drug therapies [ 129 , 130 ].…”
Section: Bdnf In Psychiatric Disordersmentioning
confidence: 99%
“…Remarkably, drug treatment that is effective in controlling disease progression in schizophrenic patients can have diverse effects on peripheral BDNF protein levels [ 126 128 ]. In addition, some studies suggest that baseline BDNF levels in schizophrenia patients might reflect the susceptibility towards available drug therapies [ 129 , 130 ].…”
Section: Bdnf In Psychiatric Disordersmentioning
confidence: 99%
“…The studies of changes in BDNF levels during treatment are controversial; only relapse schizophrenic males patients showed elevated BDNF after 4 weeks of risperidone consumption (3-6 mg/day), a result that suggests gender should be considered when choosing the pharmacological treatment (167)(168)(169). However, other studies reported no alteration whatsoever after risperidone consumption (170,171).…”
Section: Risperidonementioning
confidence: 99%
“…Olanzapine did not increase plasma BDNF in a 6‐week prospective study of schizophrenic patients (n = 50) (Kudlek Mikulic et al, ). A study of ethnically homogenous schizophrenic patients correlated olanzapine treatment with shortened leukocyte telomere length and advanced metabolic age (Monroy‐Jaramillo et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Olanzapine did not increase plasma BDNF in a 6-week prospective study of schizophrenic patients (n = 50) (Kudlek Mikulic et al, 2017).…”
Section: Olanzapinementioning
confidence: 86%